Lesões por pressão relacionadas ao uso de máscaras N95 em terapia intensiva em meio a pandemia por COVID-19 - Spadotto, Suellen de Fatima [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Introduction: The COVID-19 pandemic is responsible for causing respiratory infections that may manifest severely. The virus has a high rate of infectivity, being transmitted by droplets or aerosols, and it is necessary the correct use of personal protective equipment by health professionals. Thus, for the most severe cases, which require intensive care, professionals should wear n95 masks for a long period of time in their work shift. The use of this device may cause pressure damage in areas where the mask has exerted pressure. Objective: To evaluate pressure injuries by wearing N95 masks in health professionals working in an intensive care unit specialized in care for patients with COVID-19. Method: Cross-sectional study that evaluated the incidence of injury by mask use in professionals (physicians, nurses, nursing technicians and physiotherapists) in care for patients suspected/confirmed of COVID19. A questionnaire was applied to them in order to evaluate their particularities of the skin, as well as the development of pressure injury, its classification and risk factors for its development. The sample comprised 85 participants, who signed the Free and Informed Consent Form. For statistical analysis, the significance of p <0.1 and multiple logistic regression were considered. Results: 85 professionals were evaluated in order to verify the occurrence of pressure injury related to the use of N95, and 91.8% of them presented some type of injury and 74.1% presented nose injury and 83.5% of the cases of injury were reactive hyperemias, regarding the use of protective barriers only 27.1% used them. Professionals with black/brown color and night workers have a greater predisposition to be affected with ear injuries. Conclusion: After evaluating the data, we observed that the way of wearing the mask, the incorrect use of protective barriers, the tone and appearance of the skin may increase the chances of pressure injury

Introdução: A pandemia de COVID-19 é responsável por causar infecções respiratórias que podem se manifestar gravemente. O vírus tem alta taxa de infectividade, sendo transmitido por gotículas ou aerossóis, sendo necessária a correta utilização de equipamentos de proteção individual pelos profissionais de saúde. Dessa forma, para os casos mais graves, que necessitam de terapia intensiva, os profissionais devem utilizar máscara N95 por um longo período de tempo em seu turno de trabalho. O uso deste dispositivo pode ocasionar lesões por pressão em áreas que a máscara tenha exercido pressão. Objetivo: Avaliar as lesões por pressão por uso de máscaras N95 em profissionais de saúde que atuam em unidade de terapia intensiva especializada em atendimento à pacientes com COVID-19. Método: Estudo transversal que avaliou a incidência de lesão por uso de máscara em profissionais (médicos, enfermeiros, técnicos de enfermagem e fisioterapeutas) em atendimento à pacientes suspeitos/confirmados de COVID-19. Foi aplicado questionário aos mesmos a fim de avaliar suas particularidades da pele, assim como foi avaliado o desenvolvimento de lesão por pressão, sua classificação e os fatores de risco para seu desenvolvimento. A amostra compreendeu 85 participantes, que assinaram o Termo de Consentimento Livre e Esclarecido. Para análise estatística foi considerada a significância de p <0,1 e regressão logística múltipla. Resultados: Foram avaliados 85 profissionais a fim de verificar a ocorrência de lesão por pressão relacionada ao uso de N95, sendo que 91,8% destes apresentaram algum tipo de lesão e 74,1 % apresentaram lesão no nariz e 83,5% dos casos de lesão foram hiperemias reativas, quanto ao uso de barreiras de proteção apenas 27,1% as utilizaram. Profissionais com de cor preta/ parda e trabalhadores do noturno tem maior predisposição em ser acometido com lesões na orelha. Conclusão: Após a avaliação dos dados observamos, que a maneira de vestir a máscara, o uso incorreto das barreiras de proteção, o tom e aspecto da pele podem aumentar as chances de lesão por pressão.
Pressure injuries related to the use of N95 masks in intensive care in the middle of the COVID-19 pandemic
Keywords: Pressure ulcer; Personal protective equipment;; COVID-19; Lesão por pressão; Equipamento de proteção individual